TRANSFORMASI PERILAKU SOSIAL DAN KEAGAMAAN SISWA: DAMPAK PENGGABUNGAN KELAS SANTRI DAN SANTRIWATI DI PESANTREN - Elok Fajri Sa’diana; Lalu Agus Satriawan; Al-ghauts, Ahlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyse the transformation of students’ social and religious behaviour as a result of the implementation of co-educational classes for male and female students at the PUSTKQIH NWDI Gelogor Islamic Boarding School. The focus of the study is on changes in patterns of social interaction, character building, and the internalisation of religious values that develop within the co-educational learning system. The research employs a qualitative approach using a case study design. Data were collected through participatory observation, in-depth interviews with the boarding school leadership, teachers, male students, and female students, as well as a review of documentation related to the implementation of teaching and the boarding school’s rules and regulations. Data analysis was conducted interactively through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that the integration of male and female students’ classes makes a positive contribution to the development of students’ social behaviour. The interactions taking place in the learning environment foster mutual respect, improved communication skills, constructive cooperation, and an increased sense of responsibility in the learning process. From a religious perspective, the co-educational system strengthens self-control, awareness of Islamic etiquette, discipline, and the ability to apply moral values in daily life. The success of this model is supported by intensive teacher supervision, the consistent application of boarding school rules, and a strong religious culture within the boarding school environment. The research findings indicate that the integration of male and female students does not diminish the quality of students’ religiosity but can serve as an effective means of building a balanced socio-religious character. This study has implications for the development of a boarding school education model that is adaptive to social change without neglecting the principles of Islamic education and the moral development of students.